SEROVARS AND ANTIMICROBIAL RESISTANCE OF Salmonella spp. ISOLATED FROM TURKEY AND BROILER CARCASSES IN SOUTHERN BRAZIL BETWEEN 2004 AND 2006 - Andre PALMEIRA; Luciana Ruschel dos SANTOS; Anderlise BORSOI; Laura Beatriz RODRIGUES; Max CALASANS; Vladimir Pinheiro do NASCIMENTO (Revista do Instituto de Medicina Tropical de São Paulo, 2016)
Salmonella spp. causes diseases in fowls, when species-specific serovars (Salmonella Pullorum and S.Gallinarum) are present in flocks, and public health problems, when non-typhoid serovars are isolated, as well as possible bacterial resistance induced by the preventive and therapeutic use of antimicrobials in animal production. This study describes the serovars and bacterial resistance of 280Salmonella spp. strains isolated from turkey and broiler carcasses in Southern Brazil between 2004 and 2006. SalmonellaEnteritidis was the most prevalent serovar (55.7%), followed by Heidelberg (5.0%), Agona (4.3%), Bredeney (3.9%), Hadar (3.2%), and Typhimurium (2.9%). Tennessee and S. Enterica subspecies enterica(O: 4.5) were isolated only in turkeys, and Hadar (18.6%) was the most prevalent serovar in this species. Antimicrobial susceptibility tests were performed in 178 isolates (43 from turkeys and 135 from broilers). All isolates were sensitive to amoxicillin + clavulanic acid, polymyxin B, ciprofloxacin, and norfloxacin, and were resistant to bacitracin and penicillin. Broiler carcass isolates showed resistance to nalidixic acid (48.9%), nitrofurantoin (34.3%), neomycin (9.6%), tetracycline (5.2%), and kanamycin (8.9%); and turkey carcass isolates were resistant to nalidixic acid (62.8%), tetracycline (34.9%), and neomycin (30.2%), with a significant difference in turkeys when compared to broiler carcass isolates. These results indicate the need for judicious use of antimicrobials in livestock production, given that the serovars identified are potential causes of food poisoning.